Scared or Attached? Unraveling Important Links in Strain-Crime Relationships Among School Students - Kuptsevych-Timmer, Anastasiia (International journal of offender therapy and comparative criminology, 2019)
Drawing on general strain theory of crime, the study employs the survey data from a random sample of 600 school students in Lviv, Ukraine, to examine how sanction risks and social bonds mediate and moderate the relationship between strain and adolescent delinquency. Findings from negative binomial regressions and the KHB decomposition procedure demonstrate that fear of sanctions and levels of social control mediate the relationships between strain and delinquency to a different degree, depending on the type of strain experienced. Results concerning conditioning effects are mixed, with only parental monitoring found to be a moderator of the strain-delinquency link. However, the direction of the interaction effect is unexpected. Future research needs to improve the specification of strain models and evaluate them in other sociocultural contexts.